P012 Low frequencies of circulating inhibitory TIGIT+CD38+ effector T cells identify an immunologically distinct subgroup of pediatric patients with severe Crohn's disease. (27th May 2021) - Heredia, M; Costes, L; Tindemans, I; Aardoom, M; Klomberg, R; Kemos, P; Joosse, M; van Haaften, D; Tuk, B; Ruemmele, F; Croft, N; Escher, J; et al.
Abstract: Background: Inflammatory bowel disease (IBD), including Crohn's disease (CD) and ulcerative colitis (UC), is a T cell driven intestinal inflammation. Current T cell suppressive therapeutic regimens are moderately successful due to a large clinical heterogeneity amongst patients. Detailed understanding of aberrant inflammatory and inhibitory T-cell responses in individual patients is lacking. Previously, we have shown that, in healthy individuals, 40% of peripheral blood CD38 + (CD62L neg CD4 + ) effector T cells, which are enriched for intestinal antigen specificity, express the inhibitory molecule T cell immunoglobulin and ITIM domain (TIGIT). TIGIT + CD38 + effector T cells have a regulatory function, produce IL-10 and express multiple co-inhibitory receptors. Conversely, TIGIT neg CD38 + effector T cells are enriched in inflammatory IFN-γ producing cells. In a small cohort of pediatric-onset IBD patients, low frequencies of TIGIT + CD38 + effector T cells were associated with a reduced duration of clinical remission. We hypothesize that a subgroup of IBD patients has reduced frequencies of circulating inhibitory TIGIT + CD38 + effector T cells, reflecting a distinct pathogenesis associated with a more severe disease course. Methods: In the Rotterdam PIBD-SETQuality cohort of newly diagnosed pediatric IBD patients (CD: n=37; UC: n=16), patients with suspicion of IBD but negative diagnosis (n=12) and age-matched healthy controls (n=22), we monitored TIGIT + and TIGIT neg CD38 + effector T cells in peripheral blood and collected plasma at diagnosis and during immunosuppressive therapy. Results: At diagnosis, approximately 50% of CD patients had strongly reduced frequencies of inhibitory TIGIT + CD38 + effector T cells compared to UC patients and age-matched controls. CD patients with low frequencies of TIGIT + CD38 + effector T cells at diagnosis needed earlier anti-TNF treatment with 73% of patients receiving anti-TNF treatment within 1 year versus 38% for patients with normal frequencies of TIGIT + CD38 + effector T cells. Inflammatory TIGIT neg CD38 + effector T cells were enriched in Ki67, reflecting recent proliferation, and expressed chemokine receptors associated with inflammatory non-classical T-helper-1 IFN-γ hi IL-17 lo producing cells. High frequencies of TIGIT neg CD38 + effector T cells correlated with high plasma IFN-γ concentrations. Conclusion: These results demonstrate that reduced frequencies of circulating inhibitory TIGIT + CD38 + effector T cells discriminate a subgroup of pediatric CD patients with high frequencies of inflammatory IFN-γ hi IL-17 lo producing cells, high plasma IFN-γ concentrations, and in need of early anti-TNF treatment, possibly indicative of a distinct pathogenesis with a more severe disease course.